Soft tissue tumors - Enzinger, Franz M.; Weiss, Sharon W (St. Louis : Mosby, 1995)
General considerations -- Clinical evaluation and treatment of soft tissue tumors / Alfred E. Chang, Vernon K. Sondak -- Radiologic evaluation of soft tissue tumors / Richard P. Moser, Jr., John E. Madewell -- Molecular biology of soft tissue tumors / Paul S. Meltzer -- Cytogenetic analysis of soft tissue tumors / Jonathan A. Fletcher -- DNA analysis of soft tissue tumors / Richard J. Zarbo -- Approach to the diagnosis of soft tissue tumors -- Immunohistochemistry of soft tissue lesions -- Benign fibrous tissue tumors
Zweigstelle: Medizinische Bibliothek
Exemplar/Standort: QZ 340 Enzin (MedBib)
Exemplar/Standort: Medizinische Bibliothek
Includes bibliographical references and index
Text in engl. Sprache
Keywords: Krebs <Medizin>; Onkologie; Tumor; Weichteiltumor; Lehrbuch; Atlas